Higher Education Reform in Ethiopia: Assessing Institutional Transformation and Governance Challenges in Public Universities - Melaku Masresha Woldeamanueal; Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2025)
This study examines the higher education reforms in Ethiopia, focusing on institutional transformation and governance challenges in public universities. The purpose is to assess the effectiveness of recent policy changes and their impact on faculty satisfaction, governance, and institutional performance. The study employs a mixed-methods approach, combining quantitative analysis of governance effectiveness scores with qualitative data from interviews conducted with faculty members and administrators across several Ethiopian public universities. The findings reveal that, despite improvements in governance scores, faculty satisfaction remains low due to increased administrative burdens, lack of stakeholder engagement in decision-making processes, and a mismatch between government expectations and institutional resource allocations. Faculty reported frustration with the additional reporting requirements and policies that were perceived as disconnected from the realities of resource availability. The study concludes that while the reforms have led to structural improvements in governance, they have also introduced challenges that negatively impact faculty morale and institutional performance. It is recommended that university policymakers involve faculty more in decision-making processes, reduce administrative burdens, and provide sturdier institutional support for teaching and research activities. Additionally, sustainable research funding mechanisms and workload management policies should be implemented to enhance faculty satisfaction and prevent burnout.